Fatty acid amide hydrolase in comorbid borderline personality disorder and major depressive disorder: imaging with [11C]CURB PET - De Pol, Michelle A.; Rafiei, Dorsa; Meyer, Jeffrey H.; Desmond, Kimberly L.; McMain, Shelley; Boileau, Isabelle; Warsh, Jerry; Rusjan, Pablo; Schmahl, Christian; Vasdev, Neil; Gray, Lauren R.; Aloysius, Ryan; et al. (Neuropharmacology, 2025)
Borderline personality disorder (BPD) is highly comorbid with major depressive disorder (MDD), and the comorbid condition is associated with poorer treatment outcomes, which necessitates the investigation of transdiagnostic biomarkers. Previous research suggests that fatty acid amide hydrolase (FAAH), an endocannabinoid enzyme, is elevated in the prefrontal cortex (PFC) in BPD; however, no study has examined FAAH density in individuals with comorbid conditions. We hypothesized that FAAH level would be elevated in the prefrontal cortex, anterior cingulate cortex and hippocampus of comorbid BPD + MDD compared to healthy controls, as these brain regions are linked to the pathobiology of both disorders. For an exploratory analysis, we hypothesized that brain FAAH would be positively correlated with symptom severity, aggression, and impulsivity. Fifteen unmedicated BPD + MDD cases and 15 age- and sex-matched healthy controls underwent a [11C]CURB positron emission tomography scan to measure λk3, an index of available FAAH. No significant group differences in [11C]CURB λk3 were observed between BPD + MDD patients and controls. Negative correlations were found between [11C]CURB λk3 and physical aggression scores in the dorsolateral PFC (r = −0.64, p = 0.04), ventrolateral PFC (r = −0.75, p = 0.01), medial PFC (r = −0.64, p = 0.03), and orbitofrontal cortex (r = −0.66, p = 0.03) in the BPD + MDD group. A positive correlation was found between [11C]CURB λk3 and impulsivity, as measured by the Barratt Impulsiveness Scale-11, in the ventrolateral PFC (r = 0.62, p = 0.04) of the BPD + MDD group. We suggest that the negative correlations between [11C]CURB λk3 and physical aggression could reflect a relationship between FAAH and planned aggression whereas the latter findings may reflect a positive relationship with impulsivity.
Im Titelzusatz ist "[11C]" hochgestellt
Online verfügbar: 28. März 2025, Artikelversion: 10. April 2025
Gesehen am 07.07.2025